Interaction of student’s legal and political culture (Journal of Philosophy Culture and Political Science, 2018)
The article considers the interaction of student’s legal and political culture, identified factors affecting this relationship. Author considered scientific approaches to the interpretation of legal culture, including anthropological, sociological and philosophical. The political culture of young people is closely related to the legal culture of society. The main factors of student’s political values formation are the electronic media, family and education institutions.In addition, article determines the formation level and criteria of political and legal culture. Author determined that the development process of political and legal culture of students is carried out on the basis of unity with training and education, and concluded that Kazakhstan’s youth differ on varying degrees of political and legal culture.Key words: legal culture, political culture, students, the formation of political and legal culture, political activism, legal nihilism.